Fecal Metabolite Biomarkers for Monitoring Gut Health and Enteric Diseases in Poultry: A Systematic Review - Gunawati, Dita Novarina; Damayanti, Cindy Audina; Puspitasari, Cesaria Fitri; Haryuni, Nining; Amalta, Luky; Putri, Fitria Tridyana; Arnyke, Errythrina Vinifera (Universitas Muhammadiyah Kotabumi, 2025)
Monitoring gastrointestinal health is essential for maintaining productivity, improving disease resistance, and ensuring welfare in poultry production. Conventional diagnostic methods are often invasive, delayed, or lack sensitivity for detecting early-stage gut disorders. Fecal metabolite biomarkers offer a promising, non-invasive alternative for assessing gut health in real time. This systematic review evaluates the application of fecal metabolites in identifying enteric diseases and monitoring gut status in poultry, focusing on biomarker classes, disease links, and nutritional strategies. Relevant studies were retrieved from PubMed, Scopus, and Google Scholar, screened using PRISMA guidelines, and assessed with an adapted SYRCLE Risk of Bias tool. Ten studies met all eligibility criteria. Key metabolite groups short-chain fatty acids (particularly butyrate), histamine, amino acids, indole derivatives, and trehalose were associated with necrotic enteritis, coccidiosis, and gut dysbiosis. Nutritional interventions including inulin, resistant starch, Hermetia illucens meal, and citrus extract consistently improved metabolite profiles and intestinal integrity. Several biomarkers exhibited disease-specific patterns, suggesting diagnostic value. These findings highlight the potential of fecal metabolite biomarkers as practical tools for non-invasive gut health surveillance in poultry. Further research should focus on standardizing biomarker panels, establishing diagnostic thresholds, and integrating multi-omics approaches to enable their application in precision poultry health management.